Assessing parents, youth athletes and coaches subjective health literacy: A cross-sectional study. Issue 7 (July 2021) - Jacobsson, Jenny; Spreco, Armin; Kowalski, Jan; Timpka, Toomas; Dahlström, Örjan
Abstract: Objectives: The aim was to describe levels of subjective Health Literacy (HL), and to examine possible differences in prevalence proportions between sexes, age groups and level of educations among youth athletes and their mentors (coaches, parents/caregivers) in Swedish Athletics. Design: Cross-sectional. Methods: Data on subjective HL were collected using the Swedish Communicative and Critical Health Literacy (S-CCHL) instrument for mentors and for youth the School-Aged Children (HLSAC) instrument. Questions assessing mentors' literacy on sports injury and return to play were also included. Results: The surveys were completed by 159 (91%) mentors and 143 youth athletes (87%). The level of S-CCHL was sufficient in 53% of the mentors. Of youth athletes, 28% reported a high level of HL and the item with least perceived high HL (21%) was critical thinking. Ninety-four percent of the mentors believed that it is quite possible to prevent injuries in athletics and 53% perceived having a very good knowledge about how to prevent injuries. Forty-six percent of the mentors perceived having a very good knowledge of return to sport criteria. Conclusions: The level of health literacy was low with about half of the mentors and one out of three youth athletes having adequate HL levels. Only half of the mentors stated having a good knowledge of various injury prevention strategies. To reduce health consequences in youth sport and enable talent development more work is needed to understand the facilitators and barriers for the uptake of various health promotion and injury prevention strategies.